The impact of monetary policy and fiscal policy on economic growth in the Maghreb countries - Kheradel, Mohammed; Abdeldjalil, Touat; Azzeddin, Attia (The International tax journal, 2025)
This research investigates how fiscal and monetary policies influence economic growth across Maghreb countries — namely Algeria, Morocco, and Tunisia — during the period from 1991 to 2024. Using a panel data regression framework, the Hausman and Fisher tests indicated that the fixed-effects specification best fits the data, suggesting that each country retains distinctive structural and institutional features. After confirming the reliability of the model and the absence of econometric issues in the residual terms, the empirical findings show that fiscal policy exerts a positive but relatively modest and statistically significant influence on economic growth within the region. Conversely, monetary policy — proxied by the broad money supply — demonstrates no statistically significant relationship with economic growth. The estimates suggest that a 1% rise in government expenditure is associated with an approximately 0.0742% increase in GDP growth.